Waste Banks as a Tool for Environmental Education: A Systematic Review of Their Effectiveness, Strategies, and Implementation Challenges - Asri Alkadri; Suryo Ediyono (PT FORMOSA CENDEKIA GLOBAL, 2026)
Waste banks have emerged as an innovative community-based approach to environmental management and education, particularly in developing countries facing increasing waste generation and low public awareness of sustainable practices. This systematic review examines the effectiveness, educational strategies, and implementation challenges of waste banks as tools for environmental education. The review synthesizes findings from various studies published in recent years, focusing on how waste banks influence environmental awareness, waste sorting behavior, recycling participation, and community engagement. The findings indicate that waste banks contribute positively to environmental education by encouraging active participation, improving public knowledge about waste management, and fostering sustainable habits among students and communities. Educational strategies commonly applied include participatory learning, social campaigns, school-based activities, and economic incentives that motivate behavioral change. However, several implementation challenges remain significant, including limited financial support, inadequate infrastructure, inconsistent community participation, weak policy integration, and insufficient managerial capacity. In addition, differences in local socio-cultural conditions often affect the sustainability and effectiveness of waste bank programs. Overall, this review highlights that waste banks are not only waste management initiatives but also valuable educational instruments for promoting environmental responsibility and sustainable development. Strengthening institutional support, stakeholder collaboration, and educational integration is essential to maximize their long-term impact.